1985
DOI: 10.1002/em.2860070105
|View full text |Cite
|
Sign up to set email alerts
|

Chemical mutagenesis testing in Drosophila. II. Results of 20 coded compounds tested for the national toxicology program

Abstract: Results are presented from mutagenesis testing in Drosophila of 20 coded compounds. Two compounds were positive in the sex-linked recessive lethal test, and two were inconclusive. The positive compounds were calcium chromate in adult feeding experiments and ferrocene after adult injection. The two inconclusive compounds were 2,4-diaminophenol dihydrochloride and hexachlorocyclopentadiene. Compounds that produced a positive response were assayed for chromosome breakage using the conventional translocation test.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
2

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 7 publications
0
28
1
2
Order By: Relevance
“…In the Drosophila SLRL assay, Vogel and Chandler [1974] and Grant [1979] found this compound to be negative, whereas Majumdar and Golia [1974] and Magnusson et al [1977] report it to be positive. Zimmering et al [1985] also reported this to be negative at two doses of adult feeding and one dose by adult injection but we find that this compound is a potent mutagen in both spermatocytes and spermatogonia when fed to Drosophila larvae.…”
Section: Drosophila Melanogasteflmentioning
confidence: 76%
“…In the Drosophila SLRL assay, Vogel and Chandler [1974] and Grant [1979] found this compound to be negative, whereas Majumdar and Golia [1974] and Magnusson et al [1977] report it to be positive. Zimmering et al [1985] also reported this to be negative at two doses of adult feeding and one dose by adult injection but we find that this compound is a potent mutagen in both spermatocytes and spermatogonia when fed to Drosophila larvae.…”
Section: Drosophila Melanogasteflmentioning
confidence: 76%
“…aa. Zimmering et al [1985]; b, Valencia et al [1985]; c, Yoon et al [ 19851;d, Woodruff et al [1985]. three times we cannot make a determination of the mutagenicity of this chemical in Drosophilu.…”
Section: Resultsmentioning
confidence: 92%
“…Thus, although a first report did not obtain positive induction in the sexlinked recessive lethal test after treating adult flies [Vogel and Chandler, 1974], other authors have reported slight mutagenicity in the same test following this procedure [Magnusson et al, 1977]. On the other hand, whilst no mutagenicity was obtained when the chemical was administered by feeding and/or by injection to adults [Zimmering et al, 1985], this compound was reported to be a potent mutagen when applied during larvae development [Kale et al, 1995]. It is in this context of conflicting data where we believe that our data from using the somatic mutation assay can be relevant, mainly taking into account that the quantification of the recombining activity of a compound is of primary importance for genotoxicity screening [Graf and Würgler, 1996].…”
Section: Resultsmentioning
confidence: 83%